T Wave Peak to T Wave End Interval Is Prolonged in Patients with Atrioventricular Nodal Reentry - Yontar, O. C.; Tutuncu, A.; Karaagac, K.; Karakus, A.; Yontar, O. N. U. R.; Melek, M. (Oxford Univ Press, 2014)
…
3rd Congress of the ESC-Council-on-Basic-Cardiovascular-Science on Frontiers in Cardio Vascular Biology -- JUL 04-06, 2014 -- Barcelona, SPAIN